Analisis Kerokan Menurut Budaya dan Sains - Baiti Rizki; Atika Okta Melisa (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2021)
Traditional medicine has always been inherent in society. most pass it on to their children and grandchildren, in the hope of not dying replaced by modern medicine. Scrapings are the most popular alternative medicine. This study was conducted to find out how scrapings are carried out from the perspective of society and science, involving 50 respondents. The research method was carried out with a qualitative approach by describing the acquisition of data obtained from in-depth interviews through questionnaires supported by a literature review. The results showed that 64% of people had done scrapings and chose it because it was not only cheap but also had many benefits. In addition, from a scientific point of view, scrapings can increase tissue temperature, dilate capillaries, improve local blood circulation, increase blood and oxygen supply and strengthen local tissue metabolism. In addition, the red rash due to scraping is inflammation as a form of the body's response that does not cause skin damage.  Keywords: scrapings, culture, traditional medicine, science, medical